Development of a Web-Based Classroom Reservation System Using the Agile Scrum Methodology - Simangunsong, Gandi Abetnego; Muhammad Rafi’ Rusafni; Ghaeril Juniawan Parel Hakim; Muhammad Ilham Nurfajri; Aditya Wicaksono; Mindara, Gema Parasti (Journal of Informatics and Communication Technology (JICT), 2025)
GoClass is a web-based application designed to simplify the classroom reservation process in higher education institutions. This study aims to design and implement a system that supports efficient scheduling, approval, and analysis of classroom usage. The system development follows the Agile Scrum methodology, which emphasizes team collaboration, short development iterations (sprints), and continuous user feedback, involving stages such as sprint planning, daily stand-ups, sprint reviews, and sprint retrospectives. Unified Modeling Language (UML) diagrams—including use case, activity, and Class Diagram—were used to model system functionality and data flow. The main features developed include user authentication, real-time notifications, and room recommendations based on availability and capacity. The system also features an interactive dashboard that visualizes room usage trends, supporting data-driven decision-making.